HUBUNGAN ANTARA DERAJAT INTRAVESICAL PROSTATIC PROTRUSSION DENGAN Q MAX, VOLUME PROSTAT, DAN INTERNATIONAL PROSTATE SYMPTOM SCORE PADA PASIEN BPH DENGAN LUTS TANPA KOMPLIKASI - As'ari, Musa; Alif, Sabilal; Santoso, Adi; P, Widodo J (Indonesian Urological Association, 2016)
Objective: The prostate volume is an objective due to BPH diagnosed, however it is not always concerned with the LUTS degree. LUTS is a syndrome of BOO which marked by obstructive and irritable symptoms. The ball valve mechanism in bladder neck results in increasing of BOO. The aim of this study is to prove the relation of intravesical prostatic protrussion (IPP) with prostate volume, Q max, and international prostate symptom score (IPSS) in non complicated BPH LUTS patients. Materials and method: This research is an analysis observational that involved 85 male patients aged 50 to 91 years old (average 63,98 years old) in Urology Outpatient Clinic RSUD Dr. Soetomo, starting November 2007 until April 2008. Such IPSS evaluation, prostate volume measurement, uroflowmetry examination, and IPP examination with TAUS were applied to all of these patients. Results: The calculation shows the increasing of IPP degree followed by the decreasing of Q max value, where Spearman rank correlation indicates r=-0,465 with p=0,001 (smaller than 0,05), which shows the relation between IPP and Q max. In Spearman rank correlation, with the IPP degree increasing followed by IPSS value increasing indicates r=0,456 and p=0,001, which is smaler than 0,05. Also shows the increasing of IPP degree followed by prostate volume increasing, with r=0,230 and p=0,034 is smaller than 0,05 in Spearman rank correlation. Conclusion: The research reveals a connection between IPP degree and Q max, where the higher IPP degree the lower Q max value, the higher IPP degree the bigger IPSS value, and the higher IPP degree the bigger prostate volume.